Productivity and Resource Misallocation in Latin America - Matias Busso; Lucia Madrigal; Carmen Pages-Serra (Inter-American Development Bank (IDB), 2012)
Total factor productivity (TFP) in Latin America has not increased since the mid- 1970s, and in many countries it has declined. Moreover, resource misallocation can lower aggregate TFP. This paper presents evidence based on firm-level data from 10 Latin American countries to quantify the heterogeneity of firm productivity and the degree of resource misallocation within countries. Productivity heterogeneity and resource misallocation are found to be much larger than in the United States. Achieving an efficient allocation of resources could boost manufacturing TFP between 45 percent and 127 percent depending on the countries and years considered.
Keywords: D24; L25; O47; O54; 330